What Sherlock sorely missed: the EVA technology for cultural heritage exploration. (3rd June 2019) - Righetti, Pier Giorgio; Zilberstein, Gleb; D'Amato, Alfonsina
ABSTRACT: Introduction : Capture of proteins and metabolites from Cultural Heritage (paintings, manuscripts, parchment etc.) has been done in the past via surface scraping and erasing, a method discouraged. The EVA (ethylene vinyl acetate) method consists of a plastic polymer in which strong cation and anion resins, admixed with C8 and/or C18, are embedded. Areas covered : We review here the findings on different items stored in public libraries and archives: (a) the original manuscript of the novel Master y Margarita by Bulgakov; (b) the death registries of the lazaretto in the 1630 Milano plague; (c) the shirt worn by A. Chekhov in his death bed; (d) Kepler's script on Hipparchus (in St. Petersburg National Archives); (e) the Memoirs of G. Casanova. Expert opinion : The technique here surveyed appears to be a unique tool enabling exploration of any document stored in public archives, museum and private collections without damaging or contaminating the items under analysis. The amounts harvested from any surface are very minute, yet sufficient for analysis via advanced mass spectrometry instrumentation, thus permitting the identification of all captured material. It is hoped that the present review will stimulate the scientific community to adopt it for projects pertaining to Cultural Heritage.